Strategi Penumbuhkembangan UMKM di Nusa Tenggara Barat - Andi Pramaria (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2023)
Law Number 23 of 2014 concerning Regional Government, gives freedom to regions to carry out regional development in accordance with their potential, including economic development in their region. The main problems in regional development are improving welfare, overcoming unemployment and poverty, and income inequality. The poverty rate in West Nusa Tenggara Province in 2021 reaches 746,656 people (13.83%), while the working population reaches 2.64 million people (BPS NTB, 2022). The welfare of the community as measured by GRDP per capita reaches Rp. 18 million, while inequality in people's income is measured by the Gini Index which reaches 0.384. NTB's GRDP in 2021, shows that the agriculture, forestry and fishery sectors contribute 22%, while the processing industry only reaches 4%. This indicates that there are still many products from the agricultural, forestry and fisheries sectors that have not been processed into semi-finished goods or finished goods that are ready for consumption. Considering that large manufacturing industries are not available in NTB, it is necessary to develop MSMEs to increase added value, as well as to overcome unemployment and poverty, improve welfare and reduce inequality. Household consumption expenditures account for 64% of GRDP. If the opportunity for household consumption can be provided by MSMEs, the regional economy will move and grow.